Strategija Univerze v Mariboru 2021–2030 / Strategy of the University of Maribor 2021–2030 - v Mariboru, Univerza (University of Maribor Press, 2021)
The book can be read from both sides. One side is in Slovene language, other sides is in English language. The strategy of the University of Maribor pursues an inclusive, innovative and integrated higher education area that will train active, critically-thinking and responsible citizens, guarantee the quality of education and research, academic integrity, and cultivate concern for sustainable development of society. It stresses the importance of the freedom of research and institutional autonomy, development of lifelong learning, digitalisation and green infrastructure. It follows the orientations of the Rome Ministerial Communiqué of 2020 on the development of higher education in Europe, the Magna Charta Universitatum 2020 principles and the national strategic documents on higher education.